IMPLEMENTASI BANTUAN SOSIAL (BANSOS) DALAM UPAYA PENGURANGAN KEMISKINAN DESA BANJARBENDO - Nafilah Dzakiyah Al Azizah; Isna Fitria Agustina (Halu Oleo University, 2025)
Poverty is a significant problem in developing countries, including Indonesia, with villages such as Banjarbendo Village experiencing challenges in improving the welfare of their residents. The Indonesian government has launched various social assistance programs (Bansos) aimed at reducing poverty levels and improving the quality of life of poor people. This research uses qualitative methods with data obtained from stakeholders based on the theory of George C. Edwards III. The results obtained show that Banjarbendo Village can distribute BANSOS well so that it can reduce poverty in Banjarbendo Village.